Assessing the antiandrogenic properties of propyl paraben using the Hershberger bioassay - Özdemir, Ecem (Toxicol Res (Camb), 2018)
Propyl paraben is a widely used preservative in pharmaceuticals, cosmetics, and foods preventing microbial and fungal contamination. This study was designed to investigate antiandrogenic profiles of propyl paraben following oral doses at 10, 250, and 750 mg kg(–1) day to immature male rats using the Hershberger Bioassay. Rats were divided into six groups including solvent control, negative control (0.4 mg kg(–1) day testosterone propionate = TP), positive control (3 mg kg(–1) day flutamide = FLU) and treatment groups (10, 250, and 750 mg kg(–1) day testosterone propionate + Propyl paraben). Propyl paraben (PP) significantly decreased all accessory sex organ weights at each dose of 250 and 750 mg kg(–1) day compared to control groups. Thus, we found that propyl paraben had antiandrogenic activity within the supported results of increasing LH levels and histopathologic results such atrophy, hyalinization, and anastomosis on androgenic tissues.